EVALUASI TINGKAT PENCEMARAN LOGAM BERAT DI PERAIRAN SEKITAR AREA INDUSTRI GALANGAN KAPAL BATAM PROVINSI RIAU (Jurnal Kajian Lingkungan, 2014)
The research was conducted on December 2013. The aim is to analyze and compare the concentration of Pb, Cu, Cd and Zn in brine water, sediment and T. telescopium at several stations with different activities and determine the relationship between the concentration of heavy metals in brine water, sediment toward T. telescopium, determine the consumption feasibility of T. telescopium based on the value of PTWI (Provisional Tolerable Weekly intake) and determine the status of waters pollution by using pollution indices and standard quality guidelines. The method used was a survey method that conducted at 4 stations with 5 sampling points. The results showed that the concentration of Pb, Cu, Cd , and Zn in brine water and sediment toward the concentration of metals in T. telescopium have a positive relationship. The calculation results of the PTWI value concentration of heavy metals average in T. telescopium is still feasible for consumption while doesnât exceed the limits defined by FAO/WHO. Based on the status of pollution indices and standard quality guidelines in the waters around Batam shipyard industry is known polluted in the moderate level.Keywords: Heavy Metal Pb, Cu, Cd dan Zn, Brine Water, Sediment, T. telescopium